O jogral é jornal: devorações nas acontecências de Antonio Juraci Siqueira - Possas, Hiran de Moura (2015)
The research want to examine some artistic and journalistic trials of Antonio Juraci Smith, artist "marginal" Para over eighty publications. His empirical corpus shall emphasize twine, "Irmã Serafina Cinque: O Anjo da Transamazônica"; "Os Novos Versos Sacânicos" and "O Chapéu do Boto" as well as some short stories, essays and poems in newspapers memories, magazines and poetic anthologies. In his time delimitation, the research will follow the storyline of the artist narrated by print, by the poet himself and voices witnessing this trajectory. From these considerations, the extent to which cultural shifts in Amazons Juraci would "geometricable" and / or neo-baroque features? In the search for answers to the problems, the main hypothesis assumes that, when suturing multiple worldly voices to their Arts, Juraci now relies intercultural narrative tissues, sometimes edge scriptures "necrotic" by centripetal folklore. By the need to test, question and investigate (s) object (s) proposed (s), the following methodological assumptions considering conducting an ethnographic and cartographic were chosen: survey, the municipal public file of Bethlehem, newspapers, magazines and anthologies accepting information about the artist and his works; consulting the staff of the poet file; interviews with Juraci, researchers, craftsmen Pará; participant observation in cultural events in the streets, squares, markets, cemeteries and theaters, and "mining" of research in the light of Communication Theory in Latin America (Martin-Barbero), the Russian Cultural Semiotics (Lótman, Bakhtin), Baroque and miscegenation (Severo Sarduy, Haroldo de Campos, Lezama Lima, Alejo Carpentier, Jerusa Pires Ferreira and Amalio Pinheiro). Subsequently, the holdings of such information, the following analytical and empirical categories were extracted: the academic myopia marquetries Antonio Juraci; the joints micro-macro in Amazonian spacetimes these textures; rearticulations its cultural series using "satanic" representations, and the applicants becomings translation of the symbiotic interaction between Amazon men, animals, nature and culture. To settle the questions raised, it is expected, as of transcriadores voices of an unusual daily life, restore, in multiple forms, provisional and open to contributions, these social maps historically ignored, but full directions